Adaptive load distribution approach based on congestion control scheme in ad-hoc networks. Issue 1 (2nd January 2019) - Sharma, Varun Kumar; Kumar, Mahesh
ABSTRACT: The 'load distribution' proposition in mobile ad-hoc networks (MANETs) is accomplishing great stimulation. This is because of the phenomenal facets it possesses including advanced network resilience, reliability and performance. Though there are other leading network layer routing protocols, but they radically utilise single-path communication paradigm, which is why they fail in achieving efficient load distribution in a network. Via this paper, we propose an efficient cross-layer adaptive load distribution approach to capitalise network's channel utilisation and to rapidly adapt to dynamic wireless channel characteristic changes. The proposed method modifies the load balanced congestion adaptive routing (LBCAR) protocol and is developed using dynamic load distribution technique, by pioneering (i) novel parameters, which report for the availability of route pertaining to minimum traffic load and better link lifetime and also adapt according to varying available network resources; (ii) an absolute dynamic method to lessen the redundant route oscillations which further reduces the routing instabilities. The simulation results demonstrate the usefulness of the proposed method and yields better results in comparison to LBCAR and standard instead of dynamic ource outing, it is dynamic source routing (DSR) protocol.